An Analysis of Socio-Economic Causes and Consequences of Human Trafficking in Pakistan - GHAZALA; Shabana Tunio; Lubina Somroo (JSSH, 2024)
This research paper aims to provide a detail about the factor of commercial sexual abuse of women and children in Pakistan. The extent, prevalence, and implications of various forms of violence against women and children engaged in beggary and sex business are recorded in this report on the causes and consequences of human trafficking. The study summarizes what is known about the causes and related health consequences for each form of violence against women and children discussed. The study encourages as many systematic national assessments of the situation of violence against women and children as possible, including incidence, legal processes, child protection programs, estimates, violence in institutions, report assessment and data collection, as well as proven successful measures to protect children and deter violence against them. Consultations at the local and national levels are part of the study's planning process, with the aim of ensuring that all sectors of civil society pay more attention to violence against women and children. The study aims to generate collaborative approaches to the issue, with a focus on the South and South Asia.